Human remains from the Early Iron Age sites of Nanda and kwaGandaganda, Mngeni Valley, Natal, South Africa - Morris, A. G. (Southern African Humanities, 2021)
The remains of five individuals from Nanda and two individuals from kwaGandaganda are analysed. The bone condition of the skeletons is variable, with only the adult from kwaGandaganda, and a child from Nanda demonstrating good bone preservation. A skeleton from Nanda Test Square 7 is that of an adult woman who was probably less than 40 years of age at death. The second Nanda adult (Trench 4 Burial 1) was a man who died in his late third or fourth decade of life. The morphology of both these adults fits well within the spectrum of South African Negro populations. Trench 4 Burial 2 was that of a child of about seven or eight years at death, and Survey Point 5 produced the skeleton of an infant who died about three months after birth. Test Square 23 at Nanda produced the fragmentary remains of limb bones from an adult individual. The distinctive pattern of tooth mutilation found in the two adult crania from Nanda is of particular interest. The kwaGandaganda skeletons are those of an adult man in his 60s at death and a premature infant.